Skrining Fitokimia Ekstrak Daun Belimbing Wuluh ( Averrhoa Bilimbi ) - Yanti, Susi; Vera, Yulia (Jurnal Kesehatan Ilmiah Aufa Royhan, 2019)
Averrhoa bilimbi is one of the plants of the genus Averrhoa. Starfruit is a type of plant fruit and traditional medicine. Averrhoa bilimbi is both fruit and traditional medicine. A. bilimbi plants have been utilized by the people to cure diseases such as cough and fever. The purpose of the study was conducted to determine the content of secondary metabolites and antioxidant activity of starfruit leaves. This research is a laboratory experiment. Secondary metabolites are obtained from the extraction process, namely maceration and partitioning. Phytochemical test results on crude methanol extracts containing alkaloids, flavonoids, saponins, polyphenols, terpenoids or steroids, n-hexane fraction only contains flavonoids and steroids. ethyl acetate fraction contains alkaloids, flavonoids, polyphenols and steroids. While the positive methanol fraction contains alkaloids, flavonoids, saponins, and steroids.